2019
DOI: 10.15627/jd.2019.3
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Overall Energy Performance in Algerian Office Building Integrated Photovoltaic Window under Semi-Arid Climate

Abstract: Building integrated photovoltaic (BIPV) energy has now become one of the most significant renewable energy alternatives for providing natural daylight and clean energy. As such, this study was conducted for the first time in Algeria to experimentally evaluate the BIPV window energy and lighting energy savings of a typical office building under the semi-arid climate condition. Apart from using the Energy Plus and Integrated Environment Solution-Virtual environment (IES-VE) energy simulation tools in the experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Qiu et al [27] evaluated a proposed vacuum PV insulated glass unit using various experiments and indicated that this proposed glass unit achieved a very low U-value (around 1.5 W/m 2 .K) and cooling load reduced up to 14.20% [27]. Abdelhakim et al [28] evaluated the effect of BIPV windows on energy consumption of an office building. They indicated that these windows reduced the cooling demand of the building and provided thermal comfort during the summer season.…”
Section: Introductionmentioning
confidence: 99%
“…Qiu et al [27] evaluated a proposed vacuum PV insulated glass unit using various experiments and indicated that this proposed glass unit achieved a very low U-value (around 1.5 W/m 2 .K) and cooling load reduced up to 14.20% [27]. Abdelhakim et al [28] evaluated the effect of BIPV windows on energy consumption of an office building. They indicated that these windows reduced the cooling demand of the building and provided thermal comfort during the summer season.…”
Section: Introductionmentioning
confidence: 99%
“…The appeal of building-integrated photovoltaic (BIPV) systems is their ability to generate sustainable electricity simply by retrofitting building envelopes while simultaneously improving visual comfort [7][8][9]. Available in a variety of shapes, sizes, and designs, photovoltaic systems (PVs) blend seamlessly with commonly-used opaque and semi-transparent materials in architecture such as glass or metal, making them easy to integrate into every part of a building's envelope [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, it also requires more time, since all emissions and costs related to energy and equipment need to be calculated, considering the parameters for reducing energy demand in percent and per square meter of organic photovoltaic cells suitable for the scope this work. Abdelhakim, Kandar and Lim (2019) studied the energy performance of a commercial building in Algeria, combining the simulation method with that of measuring and verifying performance through on-site tests. If, on the one hand, this last step is crucial for the validation of the results obtained, on the other hand the methodology proposed by the authors considers a specific building, being able to provide precise design guidelines for intervention in the existing commercial building.…”
Section: Discussionmentioning
confidence: 99%
“…If, on the one hand, this last step is crucial for the validation of the results obtained, on the other hand the methodology proposed by the authors considers a specific building, being able to provide precise design guidelines for intervention in the existing commercial building. However, since the method used by Abdelhakim, Kandar and Lim (2019) differs from traditional methods only by performing performance measurement and verification, it is considered unfeasible and insufficient for the scope of this work, where multiple simulation scenarios would have to be performed manually.…”
Section: Discussionmentioning
confidence: 99%